A Prospective Evaluation of Different Frailty Indices in Patients Undergoing Transurethral Resection of Bladder Tumor - Neebal Abunaser; Adnan El-Achkar; Mohamad K. Abou Chaar,; Ali Ababneh; Sattam A. Halaseh; Ala'a Farkouh; Ramiz Abo-Hijleh; Awni D. Shahait; Samer Salah; Mohammed Shahait (Société Internationale d’Urologie Journal)
BackgroundMost studies investigating the relationship between preoperative frailty and postoperative outcomes among bladder cancer patients only assess frailty retrospectively in patients who have undergone radical cystectomy. Transurethral resection of bladder tumor (TURBT) is a commonly performed procedure in outpatient settings for a large number of bladder cancer patients. The prevalence of frailty among bladder cancer patients and its impact on postoperative complications and mortality are not well studied. MethodsTo assess the prevalence of frailty among bladder cancer patients planned for TURBT at a tertiary cancer center using the modified frailty index (mFI) and Risk Analysis Index (RAI) and further assess the impact of these indices on 30-day postoperative complications and mortality rates. ResultsBetween May 2020 and March 2021, 343 consecutive patients were enrolled. The mean age of the cohort was 64.8 ± 13.1 years, 86.6% were male, and 82% had non–muscle-invasive bladder cancer (NMIBC). The majority of the cohort (92%) was found to have low American Society of Anesthesiologists (ASA) score class (I + II), while 35.3% were labeled as frail using mFI 2+, and 32.1% based on RAI (III, IV). The 30-day readmission, postoperative complications, and mortality rates in this cohort were 3.8%, 2.3%, and 6.6%, respectively. RAI was a better indicator of mortality compared to mFI. As such, patients with low RAI score (I, II) had 0.054 odds for 30-day mortality compared to the patients with high RAI score (III, IV) (OR 0.054; CI 95%, 0.004 to 0.784; P = 0.033). ConclusionFrailty, as measured by Risk Analysis Index, is an independent predictor of early mortality in patients undergoing TURBT. Preoperative frailty assessment may improve risk stratification and patient counseling prior to su rger y.